PENGARUH STARTEGI PEMASARAN DAN KUALITAS LAYANAN TERHADAP CALON SANTRI DI PESANTREN TAHFIZH DAARUL QUR’AN LAMPUNG - Huda, Samsul; Nurman, Muhamad; Haris, Ibnu (Jurnal Manajemen Pendidikan, 2025)
In the increasingly competitive world of Islamic boarding school education, understanding how marketing and service quality influence the choices of prospective students is crucial for formulating effective strategies. Therefore, this research was conducted to delve into these two factors and offer recommendations to help the boarding school maximize its strategies. Using a quantitative approach through a survey, data was collected from 50 respondents, including prospective students and their parents. A 5-point Likert scale questionnaire was used to measure marketing strategies, service quality, and prospective students’ decisions. Multiple linear regression analysis was then applied to test the relationship between variables. The findings of the study indicate that marketing strategies (X₁) and service quality (X₂) significantly influence prospective students’ decisions (Y). The coefficient of determination (R²) of 0.643 confirms that 64.3% of the variation in prospective students’ decisions can be explained by the contribution of these two variables. This study concludes that effective marketing strategies and good service quality significantly influence prospective students’ decisions in choosing the Daarul Qur’an Lampung Tahfizh Boarding School. Therefore, the boarding school needs to continue strengthening its digital marketing strategies and improving its service quality to compete in the increasingly competitive boarding school education market.